PVC/LDPE Blends: Relationship Between Thermal/Mechanical Properties, Structure and Blend Behaviour - Román, Krisztina; Zsoldos, Gabriella (International Journal of Engineering and Management Sciences, 2019)
In this paper the effect of LDPE content in PVC foams are examined on the structure of both the foam and the LDPE. We attempt to understand how LDPE content affects the structure of PVC in blends and how it changes the glass-transition (Tg). These parameters often provide important information related to the overall macromolecular structure of the polymer blend. Thermal analytical techniques such as differential scanning calorimetry (DSC) often used to determine the structural transformation of samples. The effect of the miscibility and composition of the PVC/LDPE foam blends on the thermal stability were also investigated.